Connaissances Et Motivations Des Medecins Dans La Prescription Des Examens D’imagerie Devant Une Urgence Abdominale Non Traumatique Au Togo: A Propos D’une Enquete Realisee Aupres Des Medecins - A. Amadou; KA. Agbangba; G. Watara; L. Sonhaye; B. Tchangaï; M. Tchaou; V. Adjenou; K. N’dakena (European Scientific Journal, ESJ, 2017)
Objective: To evaluate physicians' knowledge of prescribing imaging modalities in non-traumatic abdominal emergencies. Materials and method: A transversal and analytical study, consisting of the filling of a questionnaire distributed to general physicians. The survey card included, among others, the first-line imaging modality and the most effective on four abdominal emergencies found in Togo. Results: Regarding acute appendicitis, 73% of physicians estimated the imaging needed. For 92%, ultrasound was the firstline imaging technique because of its availability according to 40%. For 87%, the scan was the most effective exam. In peritonitis, 69% of physicians considered imaging important. For 98% Conventional Chest and Abdominal Radiography was the first-line examination because 52% of physicians said it was the most available. 89% thought the CT scan was the most effective. In the case of bowel obstruction, 89% of physicians found the necessary imaging. For 96%, the first-line examination was the Conventional Chest and Abdominal Radiography because of its availability according to 51% of doctors. All physicians felt that the CT scan was the most effective examination. Concerning acute cholecystitis, 95% considered imaging very important. For 95%, ultrasound was the first-line examination. Its prescription was motivated by its availability according to 50% of doctors. 96% felt that CT was the most effective examination. Conclusion: From our study, it appears that in abdominal emergencies, imaging examinations necessary for diagnosis are prescribed according to their availability and cost, not according to their effectiveness.